Polyarteritis nodosa presenting as profuse gastrointestinal bleeding - Vaidya, Gaurang Nandkishor (BMJ Publishing Group, 2014)
A 70-year-old man presented with acute onset of profuse bleeding per rectum. An urgent colonoscopy showed blood throughout the colon and distal ileum but failed to localise the source. Subsequent visceral arteriography revealed pseudoaneurysms of the branches of the superior mesenteric artery and left gastric artery. The bleeding stopped spontaneously and the aetiology of the bleeding was later found out to be secondary to polyarteritis nodosa (PAN). The presence of profuse gastrointestinal bleeding as the sole manifestation at presentation in PAN is under-reported. Early diagnosis of PAN in patients with haemodynamically significant bleeding is necessary as prompt initiation of immunosuppressive therapy helps prevent relapses. With this case report, we highlight one of the unusual presentations of PAN and the favourable response to immunosuppression with pulsed dose steroids.